β-Lactam Combinations That Exhibit Synergy against Mycobacteroides abscessus Clinical Isolates - Story-Roller, Elizabeth (Antimicrob Agents Chemother, 2021)
Mycobacteroides abscessus (Mab) is an opportunistic environmental pathogen that can cause chronic pulmonary disease in the setting of structural lung conditions such as bronchiectasis, chronic obstructive pulmonary disease, and cystic fibrosis. These infections are often incurable and associated with rapid lung function decline. Mab is naturally resistant to most of the antibiotics available today, and current treatment guidelines require at least 1 year of daily multidrug therapy, which is often ineffective and is associated with significant toxicities. β-Lactams are the most widely used class of antibiotics and have a demonstrated record of safety and tolerability. Here, using a panel of recent clinical isolates of Mab, we evaluated the in vitro activities of dual-β-lactam combinations to identify new treatments with the potential to treat infections arising from a wide range of Mab strains. The Mab clinical isolates were heterogeneous, as reflected by the diversity of their genomes and differences in their susceptibilities to various drugs. Cefoxitin and imipenem are currently the only two β-lactams included in the guidelines for treating Mab disease, yet they are not used concurrently in clinical practice. However, this dual-β-lactam combination exhibited synergy against 100% of the isolates examined (n = 21). Equally surprising is the finding that the combination of two carbapenems, doripenem and imipenem, exhibited synergy against the majority of Mab isolates. In the setting of multidrug-resistant Mab disease with few therapeutic options, these combinations may offer viable immediate treatment options with efficacy against the broad spectrum of Mab strains infecting patients today.